On the Line and Online: Higher Non‐Response to Web‐Based Surveys Over‐Represents Avid Recreational Fishers Compared With Telephone Surveys - Ryan, Karina L.; Taylor, Stephen M.; Lyle, Jeremy M.; Stark, Kate E.; Tracey, Sean R. (Fisheries management and ecology, 2025)
ABSTRACT Recreational fishing surveys have an important role in providing data to inform fisheries management. The selection of a contact method is an important and often challenging consideration that influences the potential for non‐sampling errors that can result in unrepresentative data and biased estimates. Telephones are used for many off‐site recreational fishing surveys, but widespread use of digital technology suggests that online surveys could be a viable alternative. We compared phone surveys with alternative online surveys using probability sampling from a licence database. Response rates were lower for online surveys (13%–26%) than phone surveys (97%–98%). The proportion of respondents who reported marine fishing in the previous 12 months did not differ between survey methods (98% for both survey modes), but the proportion of avid fishers was higher for online surveys (41%–54%) than phone surveys (37%–40%). These differences reflect higher respondent burden for online surveys where data are self‐administered and respondents are more likely to opt‐out. Higher non‐response and over‐representation of avid fishers from online surveys may compromise data reliability. We recommend comparative studies to quantify and correct for biases when evaluating alternative survey modes for new or ongoing surveys.